1800'lerin Küresel Krizleri, Büyük Depresyon ve 2008 Krizi - (:unkn) unknown (My University, 2017)
Finansal krizler dünya ekonomik düzenini sarsan afetlerdir. Bu afetler toplumların yaşam standartlarını da etkilemektedir. 18. yy.'dan itibaren ulus devletlerin ortaya çıkışı ulusal ekonomileri de birbirine yakınlaştırmıştır. Karşılıklı ticaret ve buna bağlı finans ilişkilerin de artması ulusal para ve finans kurumlarını da birbiri ile olan bağlantılarını hızlandırmıştır. Fakat dönemin Klasik öğreti anlayışı par ve finans piyasalarını oluşturamamıştır. Bu yüzden 20. yy. kadar finansal krizler daha sık aralıklarla yaşanmıştır. 1930 sonrası Büyük Depresyon ve Keynesyen Devrim yetkili ulusal para kurumları olan Merkez Bankalarına müdahale yetkilerini vererek ulusal para ve finans sahalarını düzenlemeleri için tecrübe kazanmalarına olanak sağlamıştır. 20 yy. içinde yaşanan finansal krizler ise ağırlıklı iki nedenden dolayı ortaya çıkmaktadır. Birincisi küresel para ve finans sistemine hakim ülkenin hatalı para ve finans politikaları sonucunda çevresindeki ülkeleri de içine alacak şekilde ortaya çıkmaktadır. İkincisi ise serbest dolaşımlı küresel finans akımlarının düzensiz dağılımı ve yükselen Pazar ekonomilerindeki kontrolsüz dalgalanmayla krizlerin çıkmasıdır. Çalışmanın hedefi finansal krizler öncesinde yaşanan iktisadi süreçlerin incelenmesi ve bu krizlere ne tür toplum ekonomisi hareketlerinin neden olabileceğini ortaya çıkarmaktır. Olası finansal krizlere karşı nasıl hazır olunabileceği konusu da aynı zamanda tartışılacaktır.

The financial crisis are the disasters that the world economic order have convulsed. These disasters were affected infinitely the social living standarts. The emergence of the nation state from the 18th century, national economies are also closer together. Bilateral trade has accelerated and connections with each other as well as with financial institutions to increase the national currency and the related financial relationships. But the era of the classical doctrine understanding money and to regulate financial markets and to keep under control could create the appropriate authorities. So 20th Century up to the financial crisis were experienced more frequently. After the Great Depression and the Keynesian Revolution in 1930 by the competent national monetary authorities, the Central Bank has the authority to intervene to allow them to gain experience in the field of national monetary and financial arrangements. 20 yy. Financial crises are emerging in the mainly two reasons. First, global currency and the surrounding countries as a result of faulty monetary and financial policy of the country is emerging to dominate the financial system to include as well. The second is the free circulation of the current global financial crisis with irregular distribution and the emergence of uncontrolled fluctuations in emerging market economies. The object of this work is study and resarch the ecomoic process before the financial crisis and to reveal which social economic affairs are the reasons for financial crisis. Add to this object it will be discussed how the financial actors can be on the alert towards the potential financial crisis.
Global Crises of the 1800s, Great Depression and 2008 Crisis